The student’s acceptance level of smart door lock system implementation in public university hostel / Muhammad Arif Ja’afar and Zuraihana Ahmad Zawawi - Ja’afar, Muhammad Arif; Ahmad Zawawi, Zuraihana (2023)
This research investigates how well the smart door lock system is received by students living in public university residence halls, with a particular emphasis on finding adoption barriers and security concerns. The study seeks to offer insightful information that will enhance the use of technology and safety measures in dormitory settings. Data from students living in dormitories at UiTM Seri Iskandar, Perak, was gathered using a quantitative study approach and a standardized questionnaire. The results show that the smart door lock system is widely used, but there are also reservations about potential security flaws. In conclusion, solving the security issues that have been raised is essential for improving the technology's efficacy and user satisfaction. To optimize the student living experience, future research should examine longitudinal user experiences and consider combining smart door lock systems with other smart university technology.